Arsitektur Drama Rainbow: Poetri Kentjana Boelan - Irianto, Ikhsan Satria; Rifandi, Ilham; Handayani, Lusi; Gustyawan, Tofan (Prosiding Seminar Nasional Humaniora, 2023)
The architectural analysis of Soekarno's drama Rainbow: Poetri Kjencana Boelan aims to trace the design of Soekarno's dramatic work, as a preliminary study of Soekarno's dramatic vision. The material object in this research is the drama Rainbow: Poetri Kjencana Boelan while the analytical tool used is the theory of drama architecture from Ledwin, Joe and Stockadale. The research method used is a qualitative method with a text analysis approach. The result of this research is that the drama Rainbow: Poetri Kjencana Boelan has the theme of revenge, uses multi-plots (linear and episodic), designs characterizations in black and white characters and has a tragedy genre and a romantic style. The writing of the drama Rainbow: Poetri Kjencana Boelan was influenced by the spirit of the times "to destroy colonialism". Abstrak Analisis arsitektur drama Rainbow: Poetri Kjencana Boelan karya Soekarno bertujuan untuk menelusuri desain perancangan karya dramatik yang dilakukan oleh Soekarno, sebagai studi pendahuluan atas penelusuran visi dramatik Soekarno. Objek material dalam penelitian ini adalah drama Rainbow: Poetri Kjencana Boelan sedangkan piranti analisis yang digunakan adalah teori arsitektur drama dari Ledwin, Joe dan Stockadale. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan analisis teks. Hasil dari penelitian ini adalah drama Rainbow: Poetri Kjencana Boelan memiliki tema pembalasan dendam yang disusun dalam alur multiplot (linier dan episodik), penokohan dirancang dalam karakter hitam-putih dengan genre tragedy dan gaya romantik. Penulisan drama Rainbow: Poetri Kjencana Boelan dipengaruhi oleh semangat zaman "mengganyang kolonialisme".